Sentidos em circulação nas carroças do projeto “Pimp My Carroça”: por uma análise discursiva - Silva, Evelise Pereira da (2021)
In this study, we analyzed the discourses that are textualized in the carts of the project “Pimp My Carroça”, by asking ourselves how these discourses produce effects of meaning about recycling, natural environment and social criticism in the movement of the city itself, by articulating the movement of the subject-collector to the urban movement, putting at stake the language and its discursive mechanisms, affected by the symbolic, by what already makes sense, what already exists in a pre-constructed and socially legitimated social imaginary (Pêcheux, 1997a), how these discourses are textualized and circulate in the carts of the subjects-collectors of recyclable materials. These carts were revamped by this project, which is organized by the graffiti artist Thiago Mundano. This dissertation is inserted in the studies of the French Discourse Analysis, developed by Michel Pêcheux (1997a) and by Eni Orlandi (2005) and other researchers in Brazil. For this purpose, we have elected as corpus some images that are broadcasted in the website and the social networks of the project “Pimp My Carroça” (2020). In our analysis, we understand that the meanings produced from constitution processes, formulation and circulation of the discourses displayed on the carts point to a memory of the work of the subject-collectors and of the practice of recycling itself, allied to a discourse related to the environmentally correct and to the recognition of the difference in the dimension of the urban space. This memory and this environmentally correct discourse elicit a reflection on recycling and its role in the world, on the role of the subject-collectors in the society and on the invisibility of these subjects.